Kemahiran Perisian Teknologi Pemodelan Maklumat Bangunan (BIM) Dalam Industri Pembinaan Di Malaysia - Ruslan, Nur Iffah Syahirah; YAHYA, MOHD YAMANI (Research in Management of Technology and Business, 2022)
Building Information Modeling (BIM) software skills are utilised in the implementation of construction projects. This is because this technology not only enables for digital visualisation of the design but also offers all the information required for each building job. The Public Works Department (JKR) initially used this BIM programme in 2007. The software’s release has such a broad impact on the building industry that it gives several benefits to the country. This is because the usage of BIM software aids in the resolution of challenges during project construction, particularly in the early phases. The objectives of this research were to investigate the influence of BIM implementation levels on the construction industry, as well as the obstacles that construction industry stakeholders encounter while utilising BIM software in the construction industry. This study’s approach was based on an interview, which is a qualitative method. The findings showed that implementation of this software among Malaysian construction industry players is still low, with one of the obstacles being that most Malaysian construction industry players still lack skilled manpower in BIM software, and cost constraints make it difficult for industry players to invest in BIM software in a project. As a result, BIM software skills in Malaysia’s construction industry still need to be reinforced and can provide considerable advancement in the future to be on level with more developed countries.